Unraveling the invisible demon: a study of the oxidative stress markers, antioxidant activities and inflammatory markers in patients admitted with complete heart block. (25th January 2023) - Chaudhary, G; Pradhan, A K; Shah, S; Roy, S; Singh, V; Dwivedi, S K; Sethi, R; Chandra, S; Vishwakarma, P; Sharma, A K; Bhandari, M; Shukla, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Despite the recent advancements in the management of Complete Heart Block (CHB), the aetiology of CHB is still idiopathic in most of the cases. Our study explores this hitherto untouched aspect of complete heart block. Purpose: We aimed to assess the aetiological profile of Complete Heart Block patients in our study. Methods: The study population consisted of 60 patients with complete heart block aged between 30 to 80 years, attending as an inpatient in ER. Oxidative stress was measured by serum MDA, serum GSH, serum Catalase activity and serum SOD activity. Antioxidant activity was obtained by measuring the levels of serum total antioxidant capacity. Inflammatory stress was measured by IL-5 and TNF-alpha levels. These values were compared to 30 healthy controls with no prior history of smoking and diabetes mellitus. Results: The mean age of the patient was 62.48 ± 7.98 years and the gender distribution was 37 males and 23 females out of 60 patients. The mean value of serum MDA (ng/mL) in cases is 1451.26 ± 206.32, and in controls, the mean value is 1197.98 ± 234.71 (p=<0.001). The mean value of serum GSH (mcg/mL) in cases is 46.982 ± 18.613, and in controls, the mean value is 54.155 ± 10.762 (p=0.027). The mean value of serum Catalase Activity (U/min/mg protein) in cases is 10.763 ± 4.038 and in controls, the mean value is 19.878 ± 7.787 (p=0.003). The mean value of serum SOD Activity (U/g) in cases is 24.950 ± 5.4565, and in controls, the mean value is 46.214 ± 14.6309 (p=0.891). The mean value of serum Total Antioxidant Capacity (U/mL) in cases is 5.546 ± 0.620 and in controls, the mean value is 8.346 ± 2.781 (p=0.025). The mean value of serum IL-5 (pg/mL) in cases is 481.442 ± 28.8995, and in controls, the mean value is 67.347 ± 20.445 (p<0.001). The mean value of serum TNF-ALFA (pg/mL) in cases is 196.741 ± 73.771, and in controls, the mean value is 144.530 ± 42.599 (p= 0.081). Conclusions: During a complete heart block, SOD (p=0.891), CAT (p=0.003), GSH (p=0.027) and total antioxidant (TAOC) (p=0.025) were significantly decreased in cases, compared to healthy controls, thus suggesting that the elevated levels of oxidative free radicals causes endothelial dysfunctioning. The increase in ROS was observed by a highly significant increase of malondialdehyde (MDA) (p=<0.001) showing high ROS-mediated tissue damage. Besides damage by oxidative stress, our study suggests that there are certain inflammatory markers like TNF-α and IL-5 that actively participate in causing heart block. There was a significant increase in the concentration of IL-5 (p<0.001) in the cases as compared to the controls.